The International Economic System in the Historical Process and China’s Role - Li, Wei (Napredak, 2021)
The history of the construction and development of the international economic system can be traced back to the establishment of the Bretton Woods system at the end of World War II. After more than 70 years, the international economic system in different economic fields such as trade, finance and investment, as well as at the global and regional levels, has been continuously built, reformed and evolved, forming a scene of variety of current international economic system. During this period, China`s role in the international economic system has also experienced gradual changes, and has generally undergone a transformation from a bystander to a part trying to fit in, then to a participant, and finally a leader. The evolution of China`s role is not only the cause of the institutional changes in the international economic system, but also the outcome. They are complementary and closely related to each other. In the development of the international economic system, China has gradually moved from the periphery to the center, which is both an opportunity and a challenge for China.
Keywords: International economic system; institutional change; institutional strategy; China's Role